Catechol-functionalized sequence-defined glycomacromolecules as covalent inhibitors of bacterial adhesion. Issue 37 (2nd September 2020) - Fischer, Lukas; Steffens, Ricarda C.; Paul, Tanja J.; Hartmann, Laura
Abstract : Herein, we present the synthesis of catechol functionalized sequence-defined glycomacromolecules that can covalently block the binding site of lectins and bacterial adhesins. Abstract : Herein, we present the synthesis of catechol functionalized sequence-defined glycomacromolecules that can covalently block the binding site of lectins and bacterial adhesins. These structures produced on a solid phase support combine two important features: the multivalent presentation of carbohydrates for specificity, and catechols as anchors to go from highly reversible interactions to covalent attachment and more efficient inhibition. In our study we demonstrate this on the lectin Concanavalin A (ConA) by showing an increase in clustering for catechol ligands and on the effective inhibition of bacterial adhesion of E. coli on mannan surfaces by our catechol functionalized glycomacromolecules. Furthermore, covalent attachment is studied via MALDI-TOF measurements and SDS-PAGE analysis. Importantly, by replacing binding sugars with non-binding sugars, no inhibitory effects or covalent attachment were observed.